Diverse spatial, temporal, and sexual expression of recently duplicated androgen-binding protein genes in Mus musculus - Laukaitis, Christina M (BioMed Central, 2005)
BACKGROUND: The genes for salivary androgen-binding protein (ABP) subunits have been evolving rapidly in ancestors of the house mouse Mus musculus, as evidenced both by recent and extensive gene duplication and by high ratios of nonsynonymous to synonymous nucleotide substitution rates. This makes ABP an appropriate model system with which to investigate how recent adaptive evolution of paralogous genes results in functional innovation (neofunctionalization). RESULTS: It was our goal to find evidence for the expression of as many of the Abp paralogues in the mouse genome as possible. We observed expression of six Abpa paralogues and five Abpbg paralogues in ten glands and other organs located predominantly in the head and neck (olfactory lobe of the brain, three salivary glands, lacrimal gland, Harderian gland, vomeronasal organ, and major olfactory epithelium). These Abp paralogues differed dramatically in their specific expression in these different glands and in their sexual dimorphism of expression. We also studied the appearance of expression in both late-stage embryos and postnatal animals prior to puberty and found significantly different timing of the onset of expression among the various paralogues. CONCLUSION: The multiple changes in the spatial expression profile of these genes resulting in various combinations of expression in glands and other organs in the head and face of the mouse strongly suggest that neofunctionalization of these genes, driven by adaptive evolution, has occurred following duplication. The extensive diversification in expression of this family of proteins provides two lines of evidence for a pheromonal role for ABP: 1) different patterns of Abpa/Abpbg expression in different glands; and 2) sexual dimorphism in the expression of the paralogues in a subset of those glands. These expression patterns differ dramatically among various glands that are located almost exclusively in the head and neck, where the sensory organs are located. Since mice are nocturnal, it is expected that they will make extensive use of olfactory as opposed to visual cues. The glands expressing Abp paralogues produce secretions (lacrimal and salivary) or detect odors (MOE and VNO) and thus it appears highly likely that ABP proteins play a role in olfactory communication.